IL-1 TERT PROMOTER C228T MUTATION IN NEURAL PROGENITORS CONFERS GROWTH ADVANTAGE FOLLOWING TELOMERE SHORTENING IN VIVO. (3rd December 2022) - Furnari, Frank; Miki, Shunichiro; Koga, Tomoyuki; Mckinney, Andrew M; Parisian, Alison D; Tadokoro, Takahiro; Vadla, Raghavendra; Masala, Martin; Hevner, Robert F; Costello, Joseph F
Abstract: Heterozygous TERT (Telomerase reverse transcriptase) promoter mutations (TPMs) facilitate TERT expression and are the most frequent mutation in glioblastoma (GBM). A recent analysis revealed this mutation is one of the earliest events in gliomagenesis, however no appropriate human models have been engineered to study the role of this mutation in the initiation of these tumors. To address this, we established GBM models by introducing the heterozygous TPM in human induced pluripotent stem cells (hiPSCs) using a two-step targeting approach in the context of GBM genetic alterations, CDKN2A/B and PTEN deletion, and EGFRvIII overexpression. Orthotopic injection of neuronal precursor cells (NPCs) derived from hiPSCs with TPM into immunodeficient mice did not enhance tumorigenesis compared to TERT promoter wild type (TPW) NPCs at initial in vivo passage which we attribute to relatively long telomeres. We further show that the TPM mutation recruited GA-Binding Protein (GABPA) and engendered low-level TERT expression, resulting in enhanced tumorigenesis upon secondary passage and maintenance of short telomere length as has been reported in human GBM. RNA sequencing of harvested tumors grown as secondary spheres demonstrated upregulated proliferation and mitosis pathway signatures in TPM cells, consistent with their increased in vitro proliferation relative to TPW counterparts. Finally, when secondary TPM and TPW sphere cultures were reinjected into mice, only the TPM led to tumor formation. In summary, our novel GBM model illustrates a growth advantage imparted by heterozygous TPMs in the context of GBM driver mutations relative to isogenic controls, and thereby allows for the identification and validation of TERT promoter-specific vulnerabilities in a genetically accurate background.